Tafsir Modern Perspektif Mun’im Sirry dalam What’s Modern about Modern Tafsir? A Closer Look at Hamka’s Tafsir al-Azhar - Umi Wasilatul Firdausiyah (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2020)
Study of the verses of Qur’an will never run out anytime, becauseQur’an is a salih likulli zaman wa makan that is always needed toanswer the problems of times. The purpose of this study is to find outthe essence of modern interpretation which presented by Mun’im(1971), while the type of research chosen in this study is a libraryresearch which is studied with an analytical-descriptive method topresent the explanations related to modern interpretation in Mun’imSirry’s view, assisted by Hans George Gadamer’s theory, especiallyin his pre-understanding theory and his horizon theory as a bridgeto dissect Sirry’s thoughts regarding modern interpretation. Theresult research show that the interpretation of Qur’an has beencontinuously carried out by mufasir or commentators to solve thechallenges modern era. By producing interpretive works that arecompatible with each era. In the interpretation Mun’im Sirry’s,not all interpretations which born in this modern era can becategorized as modern, modern interpretations is the extent ofthese interpretations that have contribution to modern reality. Hecontinued, the Quran interpretation at the moment is almost nodifferent from the classical interpretation.